Distinções entre modalidade deôntica objetiva e subjetiva no português falado: o caso do verbo 'dever' - Gasparini-Bastos, Sandra Denise [UNESP] (My University, 2014)
The modal distinctions proposed by Hengeveld (2004), reexamined by Hengeveld and Mackenzie (2008) within the Functional Discourse Grammar (FDG), consider the existence of five types of modality: facultative, deontic, volitive, epistemic and evidential. Taking into special account the deontic modality, there are evidences that it can be subdivided into objective and subjective, as analyzed by Olbertz and Gasparini-Bastos (2013) in auxiliary constructions of spoken Spanish. This wok aims to investigate the contextual elements that favor the interpretation of these two values when they are expressed by the modal auxiliary verb “dever” (must) in spoken Portuguese data.

As distinções modais propostas por Hengeveld (2004), retomadas em Hengeveld e Mackenzie (2008) dentro da Gramática Discursivo-Funcional, consideram a existência de cinco tipos de modalidade: facultativa, deôntica, volitiva, epistêmica e evidencial. Observando-se especialmente a modalidade deôntica, há evidências de que essa modalidade pode ser subdividida em objetiva e subjetiva, como já analisado por Olbertz e Gasparini-Bastos (2013) em construções auxiliares do espanhol falado. O presente trabalho tem por objetivo investigar os elementos contextuais que favorecem a interpretação dos dois valores quando expressos por meio do verbo auxiliar modal dever em dados do português falado.
Keywords: modalidade deôntica; modalidade objetiva; modalidade subjetiva; Gramática Discursivo-Funcional; verbo dever; deontic modality; objective modality; subjective modality; Functional Discourse Grammar; verb “dever”